Factors that contribute to winning medals in international soft tennis events - Kusubori, S.; Tanaka, T. (International Journal of Racket Sports Science, 2023)
Soft tennis has four major international events, and to date, 29 official international events have been held. During this period, 576 medals have been awarded. In this study, a two-stage analysis was conducted to explore the factors that contribute to the awarding of medals. Due to the highly skewed distribution of medals, decision tree induction was employed. First, five potential variables were examined for the 10 countries that have experienced medal awards. The results showed that the "Host" effect is not a factor for winning medals, but just a norm of international soft tennis events due to the data bias caused by the extreme concentration of host countries among top four. On the other hand, we found that participation in at least 16 international events is necessary to win a medal. An interesting result for Chinese Taipei (CTP) was found that whether the court surface type is "Hard" or not was a contributing factor for winning more medals. In the second step, we examined the distribution of gold medals for the top four countries which have experienced gold medal awards. The results showed that South Korea (KOR) has won more gold medals on clay courts, and CTP on hard courts than the other courts, respectively. This study determines the effect of court surfaces on winning medals at a national level. It was also found that KOR has won more gold medals at the World Championships and Asian Games than at the other international events. Japan, on the other hand, has won more gold medals at the Asian Championships.